1995
DOI: 10.1017/s1323358000019986
|View full text |Cite
|
Sign up to set email alerts
|

An H I Mosaic of the Small Magellanic Cloud

Abstract: This paper describes the first results from a 20 deg2 mosaic of the Small Magellanic Cloud (SMC) in the λ21-cm line of neutral hydrogen. The mosaic consists of 320 separate pointings with the 375-m array of the Australia Telescope Compact Array. The angular resolution is 1′· 5 (26 pc, for a distance of 60 kpc) and the velocity resolution is l·6kms−1. The images reveal a structure of remarkable complexity, with much of the spatial power contained in high-brightness temperature compact knots and filaments. Numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
131
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(147 citation statements)
references
References 9 publications
16
131
0
Order By: Relevance
“…We confirm the findings of C06 about the discontinuity in the spatial distribution of younger clusters in the supershells 37 A and 304 A. That is, the youngest objects are found toward the eastern rim of the shell (37A) where gas and dust are located (Staveley-Smith et al 1997;Stanimirovic et al 1999) and toward regions luminous in Hα. Such HII regions visible in Hα indicate the presence of massive stars (e.g., OB-stars, supergiants, luminous blue variable stars), supernova remnants, or diffuse ionized nebulae.…”
Section: Spatial Age Distribution Smcsupporting
confidence: 90%
“…We confirm the findings of C06 about the discontinuity in the spatial distribution of younger clusters in the supershells 37 A and 304 A. That is, the youngest objects are found toward the eastern rim of the shell (37A) where gas and dust are located (Staveley-Smith et al 1997;Stanimirovic et al 1999) and toward regions luminous in Hα. Such HII regions visible in Hα indicate the presence of massive stars (e.g., OB-stars, supergiants, luminous blue variable stars), supernova remnants, or diffuse ionized nebulae.…”
Section: Spatial Age Distribution Smcsupporting
confidence: 90%
“…Its isolation from other regions of massive star formation and the relatively simple surrounding Hi shell structure encouraged us to try to constrain the processes that may have led to its formation. Using the shell catalog derived from the 21 cm neutral hydrogen (Hi) spectrum survey data (Staveley-Smith et al 1997;Staminirovíc et al 1999) we identified a distinct Hi cloud component that is likely the progenitor cloud of the cluster and the Hii region which probably formed in blister fashion from the cloud's periphery. A comparison between Hi and Hii kinematics suggests that star formation in NGC 602 was triggered by compression and turbulence associated with Hi shell interaction ∼ 7 Myr ago (Nigra et al 2008).…”
Section: Ngc 602 Kinematicsmentioning
confidence: 99%
“…concentrated towards this part of N66 (Staveley-Smith et al 1997;Stanimirović et al 1999;Gouliermis et al 2008). The H i…”
Section: Morphologymentioning
confidence: 93%